Boundary Controllability of Nonlinear System in Quasi-Banach Spaces - Taha, Abdul Wahab (Iraqi Journal of Science, 2024)
Sufficient conditions for boundary controllability of nonlinear system in quasi-Banach spaces are established. The results are obtained by using the strongly continuous semigroup theory and some techniques of nonlinear functional analysis, such as, fixed point theorem and quasi-Banach contraction principle theorem. Moreover, we given an example which is provided to illustrate the theory.